Fragment Based HQSAR Modeling and Docking Analysis of Conformationally Rigid 3-azabicyclo [3.1.0] Hexane Derivatives to Design Selective DPP-4 Inhibitors - Ghate, Manjunath; V. Jain, Shailesh (Letters in Drug Design & Discovery, 2014)
Development of potent, selective and orally bioactive dipeptidyl Peptidase IV inhibitors as antihyperglycemic agents is challenging task due to potential side effects are associated with them. It may result from other prolyldipeptidases of DPP-4 include DPP-2, DPP-8 and DPP-9. To resolve the selectivity issue in different DPP enzymes hologram quantitative structure-activity relationship studies were carried out on a series of potent and selective DPP-4 ligands. To measure selectivity between two kinds of enzyme selectivity data of DPP-4 over DPP-2, DPP-8 and DPP-9 were calculated and best HQSAR models were generated with significant correlation coefficients. The statistical results of the three models showed the best prediction and fitness for the selectivity activities. Docking studies were carried out on conformationally rigid 3-azabicyclo [3.1.0] hexane derivatives which suggested the substitution pattern on P1 and P2 fragment. The finally QSAR model, along with the information obtained from contribution maps and docking studies should be useful for the design of novel DPP-4 ligands having improved selectivity without side effects.
Keywords: Selectivity